Stress and vibration analysis of meshed gears by finite element analysis - Ong, Jimmy Pin Ren (Nanyang Technological University, 2023)
Gears are mechanical components that transmit torque and rotational motion from one machine part to another. They are widely used in a variety of machines including automotive and industrial machinery. Some common types of gears include spur gears, helical gears, bevel gears, worm gears, and rack and pinion gears. Each type of gear has their own unique characteristics, making it suitable for different applications. Spur gears are the most commonly used in industry as it is easy to manufacture and has high efficiency in transmitting power and torque. In this final year project, spur gear is used for analysis. The maximum von-Mises stress at the tooth contact, displacement of the center of pinion shaft and center of gear shaft, and natural frequency of spur gear assembly are studied using finite element analysis. The software ANSYS Workbench 2022 R1 academic version is used. A 3D model of meshed spur gear is built and subjected to static torsion loading. Mesh refinements are carried out at the tooth of the gear as well as at the shaft body. Parameters such as length of shaft and applied torque are varied to see how they affect the three results as mentioned above. The mode shapes are also studied to see how gears vibrate at various frequencies. It is observed from the results that as the length of the shaft is shortened, the displacement of the center of both shafts decreases and the natural frequency increases. The maximum von-Mises stress at the tooth contact does not have a relationship as it increases and decreases non-uniformly when the length is decreased. Next, when the torque applied at the input shaft increases, the maximum von-Mises as well as the displacement of the center of the shafts increases. The natural frequency is not affected by the increase in torque as it remains almost constant.